Eustress - Ikhide, Juliet Eyore; Ogunmokun, Oluwatobi A. (Edward Elgar Publishing Ltd., 2022)
[Abstract Not Available]
Keywords: eustress; positive stress; service employees; stressors; tourism stress; tourists